Biosurfactant Production And Plasmid Isolation From Newly Isolated Hydrocarbonoclastic Bacteria Proteus inconstans - Padmapriya, B. (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTBiosurfactant are surface active agent that are produced extracellularly or as part of the cell membrane by bacteria, yeast and fungi. In the present study, hydrocarbonoclastic bacteria were isolated from petroleum contaminated sites nearby petrol bunks in Chidambaram. Screening of biosurfactant producing potential strain was done by haemolytic assay and bath assay and the potential strain was identified by biochemical tests as Proteus inconstans. After optimizing the biomass production in different physical and chemical parameters, the mass production of biosurfactant was carried out along with biodegradation and emulsification of crude oil. The ability of strain Proteus inconstans to grow and produce biosurfactant on different carbon sources, temperatures and pH was studied. In this study, the biosurfactat productivity was 0.8mg/ml in cultures grown in a medium supplemented with glucose adjusted to pH 7.0 and incubated at 37Âº. The productivity at the optimum condition. Fourier Transform Infrared Spectroscopy & Mass Spectrometric Analysis were carried out which confirmed the glycolipid nature of the biosurfactant. The plasmid with 1.8Kbp was isolated from the strain and it was cured by acridine orange. Biodegradation and biosurfactant activities were totally inhibited. Hence it was determined that the biosurfactant production was purely plasmid mediated.